The French-speaking world a practical introduction to sociolinguistic issues - Ball, Rodney; Marley, Dawn (Routledge, Taylor & Francis Group, 2017)
This new edition has been fully revised to reflect the many political and social changes of the last 15 years, including the impact of technology on language change. It continues to combine text with practical exercises and discussion questions to stimulate readers to think for themselves and to tackle specific problems.